Flavokawain A induces apoptosis in MCF-7 and MDA-MB231 and inhibits the metastatic process in vitro - Abu, Nadiah; Akhtar, Muhammad Nadeem; Yeap, Swee Keong; Lim, Kian Lam; Ho, Wan Yong; Zulfadli, Aimi Jamil; Omar, Abdul Rahman; Sulaiman, Mohd Roslan; Abdullah, Mohd Puad; Mohamed Alitheen, Noorjahan Banu (Public Library of Science, 2014)
Introduction: The kava-kava plant (Piper methsyticum) is traditionally known as the pacific elixir by the pacific islanders for its role in a wide range of biological activities. The extract of the roots of this plant contains a variety of interesting molecules including Flavokawain A and this molecule is known to have anti-cancer properties. Breast cancer is still one of the leading diagnosed cancers in women today. The metastatic process is also very pertinent in the progression of tumorigenesis. Methods: MCF-7 and MDA-MB231 cells were treated with several concentrations of FKA. The apoptotic analysis was done through the MTT assay, BrdU assay, Annexin V analysis, cell cycle analysis, JC-1 mitochondrial dye, AO/PI dual staining, caspase 8/9 fluorometric assay, quantitative real time PCR and western blot. For the metastatic assays, the in vitro scratch assay, trans-well migration/invasion assay, HUVEC tube formation assay, ex vivo rat aortic ring assay, quantitative real time PCR and western blot were employed. Results: We have investigated the effects of FKA on the apoptotic and metastatic process in two breast cancer cell lines. FKA induces apoptosis in both MCF-7 and MDA-MB231 in a dose dependent manner through the intrinsic mitochondrial pathway. Additionally, FKA selectively induces a G2/M arrest in the cell cycle machinery of MDA-MB231 and G1 arrest in MCF-7. This suggests that FKA's anti-cancer activity is dependent on the p53 status. Moreover, FKA also halted the migration and invasion process in MDA-MB231. The similar effects can be seen in the inhibition of the angiogenesis process as well. Conclusions: FKA managed to induce apoptosis and inhibit the metastatic process in two breast cancer cell lines, in vitro. Overall, FKA may serve as a promising candidate in the search of a new anti-cancer drug especially in halting the metastatic process but further in vivo evidence is needed.